2011
DOI: 10.1155/2011/230840
|View full text |Cite
|
Sign up to set email alerts
|

Management of Kikuchi-Fujimoto Disease Using Glucocorticoid: A Case Report

Abstract: Kikuchi-Fujimoto disease, also known as histiocytic necrotizing lymphadenitis, is a self-limiting, benign, and rare systemic lymphadenitis with unknown etiology. The cardinal symptoms are fever, lymphadenopathy and night sweat; consequently, it is first necessary to rule out infectious, lymphoproliferative, and connective tissue diseases such as systemic lupus erythematosus. Histology can allow diagnosis by demonstrating necrotizing histiocyte lymphadenitis. Disease, which has no specific treatment, self-limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 2 publications
1
21
0
1
Order By: Relevance
“…High dose glucocorticoids with intravenous immunoglobulin have been shown to have some benefit in severe symptoms. In supportive treatment, non-steroid anti-inflammatory drugs may be used to alleviate lymph node tenderness and fever [1,19,20]. Kuo T., et al reported that, although KFD is essentially a self-limiting illness, there is a 3% risk of recurrence [8].…”
Section: Discussionmentioning
confidence: 99%
“…High dose glucocorticoids with intravenous immunoglobulin have been shown to have some benefit in severe symptoms. In supportive treatment, non-steroid anti-inflammatory drugs may be used to alleviate lymph node tenderness and fever [1,19,20]. Kuo T., et al reported that, although KFD is essentially a self-limiting illness, there is a 3% risk of recurrence [8].…”
Section: Discussionmentioning
confidence: 99%
“…Literature discusses both viral and autoimmune causes as the most likely. The role for viruses like Epstein-Barr virus, human herpesvirus 6 and 8, parvovirus B-19, parainfluenza and paramyxoviruses is controversial and, unremarked [5,6]. KFD has also been reported in patients with AIDS [7].…”
Section: Discussionmentioning
confidence: 99%
“…La EKF es, generalmente, de curso autolimitado y ningún tratamiento efectivo ha sido establecido. En cuadros severos o persistentes, los glucocorticoides orales han mostrado mejoría al acortar la duración de los síntomas [43][44][45][46] , sin existir estudios randomizados al respecto. Un estudio trató con bolos de metilprednisolona a 13 pacientes, observando resolución de la fiebre en 24 h 46 .…”
Section: Discussionunclassified